A diachronic investigation of 'local' pottery production and supply at the sanctuary of Zeus, Mount Lykaion, Arcadia, Peloponnese. (June 2016) - Kordatzaki, G.; Kiriatzi, E.; Müller, N.S.; Voyatzis, M.; Romano, D.; Petrakis, S.; Forsén, J.; Nordquist, G.; Rodriguez-Alvarez, E.; Linn, S.
Abstract: The present paper reports results of an integrated study of a selection of pottery recovered from the altar of Zeus, Mount Lykaion, Arcadia, in the Peloponnese, Greece, dating from the Neolithic to the Early Iron Age. A multi-analytical approach based on petrographic and chemical analysis, supported by refiring tests and geological sampling, has been employed to tackle issues of technology and provenance. Results shed light on patterns of raw material sources exploitation and pottery production and supply at the site over time. Highlights: A multi-analytical approach has been employed to tackle issues of provenance and technology. Petrographic and chemical analyses were applied on pottery samples. These techniques were supported by refiring tests and geological sampling. A shift is suggested through time from highland to lowland sources exploitation.